(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
This paper discusses the various provisions of maintenance for Muslim wife after dissolution ofmarriage under Muslim law in India. This is a descriptive study based on secondary research. Muslimwomen’s maintenance is primarily governed by the provisions of Muslim Women (Protection of Rights onDivorce) Act, 1986. Earlier it was covered under Section 125 of Cr.P.C, 1973. The paper elaborates theright to maintenance after dissolution of marriage based on different ways of dissolution- death ofhusband, divorce and Apostasy. Different Muslim laws, ie., Hanafi Law, Shia and Shafie law, Dissolutionof Muslim Marriage Act, 1939) deal differently with Muslim women’s maintenance in case of dissolution.